Analisis Kontribusi Keuntungan Atas Produk-Produk Pada Usaha Penggilingan Daging Titipane Gusti Di Kota Bangun (Penerapan Linear Programming Metode Simpleks) - Setiawan Budi Tri Wahyono; Iskandar Iskandar; Raudatul Adawiyah (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2017)
Abstract:The main objective of this research is to know how much each milled ground beef production and milled chicken meat to maximize the profit on the products At Meat Milling Enterprise Titipane Gusti In Kota Bangun. The result of data analysis in this study shows that the company will get the maximum benefit from the Milling Beef (A1) product with optimum production 271 kg in 1 week resulting in total sales of Rp. 86.720.000, - net profit of Rp. 16.260.000, - and milled beef (A3) with optimum production 149 Kg in 1 week yielding total sales equal to Rp. 50.660.000, - net profit of Rp. 5. 960.000, -. This business will generate per week with total sales of Rp. 137.380.000, - and get the maximum profit of Rp. 22.220.000, - Another case for products showing in optimal production of 0 (zero) this means that the product is better not produced by the company because it does not generate maximum profit. If the company has many inputs used to perform production activities with the ultimate goal is to get maximum profit then the analytical tool that can be used is with linear programming simplex method. Keywords: Profit Contribution (Liniear Application Programming Simplex Method)